Os loteamentos urbanos de acesso controlado e seus impactos no uso de espaços públicos segregados, no município de Manaus - Cromwell, Adriana Carla Souza (2018)
The urban centers experience in the last decades expressive process of expansion, causing intense growth of the cities. This scenario contributes significantly to the urban areas of cities developing in a disorderly way, leading to accelerated growth with significant increase of its inhabitants, generating major environmental problems related to infrastructure, housing, urban mobility, transportation, among others. Despite the constitutional guarantee of decent housing, urban reality shows a great contradiction between ample green spaces, served by adequate infrastructure for housing settlement (usually destined to plots of the population with better economic situation), with green areas and leisure, as opposed to majority of individuals, who eventually settle in improvised informal housing outside the urban legality and with inevitable environmental degradation and low quality of life. In this scenario, in search of greater security, allotments arise, (with the installation of gates and/or guaritas with access control), to, without legal protection, transform them into 'de facto condominiums', known as 'closed lots', depriving the population surrounding the right to enjoy the public spaces inserted in these spaces. However, Law No. 13,465 / 2017 was recently enacted, instituting a new modality of land subdivision, called 'controlled access land subdivision', legitimizing the old 'closed subdivisions'. In this context, the present research investigates how the local community can have guaranteed and realized the right to the usufruct of the public areas inserted in these spaces and what the legal solution to assure the right of the individuals who live outside these allotments to fruir of spaces like squares, streets and leisure areas, whose access is restricted to residents of the new kind of subdivision. The research line chosen is the conservation of natural resources and sustainable development. The scientific method is the deductive; the means of bibliographical and documentary research; and as for the ends, qualitative. KEYWORDS: Environment; Urbanistic; Allotment; Public spaces.